Species Endemism: Predicting Broad-Scale Patterns and Conservation Priorities - Zuloaga Villamizar, Juan Gerardo (Université d'Ottawa / University of Ottawa, 2018)
Do thermal barriers limit biotic composition and community similarity, potentially helping to shape biodiversity patterns at continental scales? Are environmental variables responsible for broad-scale patterns of species endemism? Are these patterns predictable? And, how can patterns of endemism can inform global conservation strategies? These are some of the questions that I attempted to answer during my doctoral research. In the first chapter, I tested one of the most contentious hypotheses in ecology: Do thermal barriers, which grow stronger along elevational gradients across tropical mountains, create a dispersal barrier to organisms and consequently contribute to the isolation and divergence of species assemblages? If so, do patterns potentially generated by this mechanism detectably relate to dissimilarity of biotic assemblages along altitudinal gradients across the mountains in the Americas? We found that mountain passes are not only higher in tropical realms, as initially thought by Janzen (1967), and extensively popularized and assumed in further research, but they are also present in temperate regions along the western coast of North America. We also found that the stronger the thermal barrier, the higher the dissimilarity between communities. However, the variance explained was low, suggesting thermal barriers play a minor role in creating and maintaining patterns of biodiversity. The second chapter raises the question of why are there more small-ranged species in some places than in others. I tested four macroecological hypotheses (H1: climate velocity; H2: climate seasonality; H3: climate distinctiveness or rarity; and, H4: spatial heterogeneity in contemporary climate, topography or habitat) to predict broad-scale patterns of species endemism, using a cross-continental validation approach. We found that there is no empirical reason, from the standpoint of model fitting, parameter estimates, and model validation, to claim that any of these hypotheses creates and maintains broad-scale patterns of endemism. Although we found statistically significant relationships, they failed stronger tests of a causal relationship, namely accurate prediction. That is, the hypotheses did not survive the test of cross-continental validation, failing to predict observed patterns of endemism. Climate velocity was dropped from some models, suggesting that early correlations in some places probably reflect collinearity with topography. The effect of richness on endemism was in some cases negligible, suggesting that patterns of endemism are not driven by the same variables as total richness. Despite low explained variance, spatial heterogeneity in potential evapotranspiration was the most consistent predictor in all models. The third chapter is aimed to evaluate the extent to which global protected areas (PAs) have included endemic species (species with small range size relative to the median range size). We measure the relative coverage of endemic species by overlapping species geographic ranges for amphibians, mammals, and birds, with the world database of PAs (1990-2016). Then we measure the rate of expansion of the global PA network and the rate of change in endemic species coverage. We found that ~30% of amphibian, ~6% of bird and ~10% of mammal endemic species are completely outside PAs. Most endemic species’ ranges intersect the PA network (amphibian species = 58%; birds = 83%; mammals = 86%), but it usually covers less than 50% of their geographic range. Almost 50% of species outside the PA network are considered threatened (critically endangered, endangered and vulnerable). We identified that ecoregions in tropical Andes, Mesoamerica, Pacific Islands (e.g., New Guinea, Solomon), Dry Chaco, and Atlantic forests are major conservation priorities areas. The historic rates of new PAs added every year to the network is between ~6,000 to ~15,000. In contrast, we found that rates of including endemic species within the PA network have been fairly slow. Historic data shows that every year, the entire geographic range of 3 (amphibians) to 6 (birds and mammals) endemic species is 100% included inside the PA network (amphibians = from 162 to 233; mammals = 10 to 84; and, amphibians = 16 to 99). Based on these trends, it is very unlikely PAs will include all endemic species (14% total endemic species, that is ~1,508 out of 11,274) currently outside the PA network by 2020. It will require five times the effort made in the last two decades. However, projections also showed that is very likely that some portions of the geographic ranges for all endemic birds and mammals, but not for all endemic amphibians, will be covered by the future PA network. I sum, I found that none of the hypotheses tested here can explain broad-scale patterns of total species richness and total species endemism. My main contribution on this research area is clearly rejecting these hypotheses from potential candidates that may explain biodiversity patterns. By removing them, we advance in this field and open possibilities to test new hypotheses and evaluate their mechanisms. I proposed that other drivers and mechanisms (whether biotic and biotic) acting at local scales, and escaping the detection of macroecological approaches, might be responsible for these patterns. Finally, in terms of conservation planning, I proposed that the international community has an opportunity to protect a great number of endemic species and their habitats before 2020, if they strategically create new PAs.
Keywords: Macroecology; Endemism; Endemic; Amphibians; Mammals; Birds; Climate stability; Climate distinctiveness; Climate velocity; Conservation; Protected areas; spatial heterogeneity; Biodiversity; Mountain passes; Biotic dissimilarity; Mountains; Species richness; Species distributions